Student support in higher education: campus service utilization, impact, and challenges. Issue 12 (December 2022) - Johnson, Chithira; Gitay, Rizwan; Abdel-Salam, Abdel-Salam G.; BenSaid, Ahmed; Ismail, Radwa; Naji Al-Tameemi, Rusol Adil; Romanowski, Michael H.; Kazem Al Fakih, Batoul Mohamad; Al Hazaa, Khalifa
Abstract: Worldwide, university student support services facilitate student performance, contribute to students' success, and increase students' chances of degree completion. Student support services programs' success depends on students' help-seeking behavior. This study explores the help-seeking behavior of Foundation Program and Undergraduate students at Qatar University (QU) through their use of campus services to better understand students' use of these services. The study examines the association between help-seeking behavior, as indicated through services, on student success and persistence in two consecutive semesters, Spring 2019 and Fall 2019. Findings report a significant association between students' services and student success and persistence. A significant difference was reported between at-risk students' majors and at-risk students in STEM and non-STEM majors. Also, there was a difference in the help-seeking behavior among males and females, nationals and non-nationals, and student classifications. Abstract : Student support; Campus services; At-risk students; STEM.